2015
DOI: 10.1016/j.jweia.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simplifications on isolated wheel aerodynamics

Abstract: a b s t r a c tIn order to study the aerodynamic forces and flow features of rotating wheels, compromises and simplifications are often made in wind tunnel testing, and more frequently so in numerical modelling. A CFD approach similar to that commonly used in industry was utilised to investigate common assumptions involving; the influence of geometric fidelity in wheel hub regions, ground representation, the modelling of the contact patch, and the effects of rotation on separation. It was found that the separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Geometry used by Fackrell and Harvey was simplified for numerical analysis by Axon et al (1998). Diasinos et al report that in order to better study the impact of factors like groove dimensions and corner radii, etc., the simplification of model geometry is very useful (Diasinos et al, 2015). Therefore, based on the recommendations of Axon et al, a simplified tire geometry for current experimentation has been deployed as shown in Figure 1.…”
Section: Geometry Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometry used by Fackrell and Harvey was simplified for numerical analysis by Axon et al (1998). Diasinos et al report that in order to better study the impact of factors like groove dimensions and corner radii, etc., the simplification of model geometry is very useful (Diasinos et al, 2015). Therefore, based on the recommendations of Axon et al, a simplified tire geometry for current experimentation has been deployed as shown in Figure 1.…”
Section: Geometry Selectionmentioning
confidence: 99%
“…Both the rotating and the separating flow phenomena occur in our computer-simulated experiments. The comparison between different turbulence models on tire model is given by Diasinos et al (2015). The Realizable K-ε RANS model is used to solve complex flows by different studies (Doig and Barber, 2011;Blocken and Toparlar, 2015;Diasinos et al, 2017).…”
Section: Numerical Model Configurationmentioning
confidence: 99%
“…There are four main computational techniques of comprehensively modelling the flow around the rotating wheels. The rotating boundary condition 3,10,17 and moving reference frame 18 are popular due to their simple implementation, mainly employed for steady state approximations. The sliding mesh approach 19 enables time-depended simulations where fixed and moving spatial domains can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Contact modelling would be ideally represented by two tangent surfaces; however, in practice, this usually leads to the incurrence of extremely small elements in the vicinity of the contact area, with element of high skewness as McManus and Zhang 10 and Mears and Dominy 15 experienced with their computational models. One of the most popular solutions is the use of an artificial step as a transition between the wheel and the ground; Diasinos et al 3 and Heyder-Bruckner 17 demonstrated this technique and its implementation. Axon et al 1 defined a wall velocity on the contact patch so that the discontinuities between the tangential velocity of the tyre and the moving ground are minimised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation